Towards green roads in Malaysia : review of road characteristics effects on road surrounding microclimate with respect to roadside trees / Nasibeh Faghih Mirzaei ... [et al.] - Mirzaei, Nasibeh Faghih; Syed Fadzil, Sharifah Fairuz; Abdullah, Aldrin; Taib, Nooriati; Esmaeilifar, Reza (2015)
Due to the rapid Malaysian metropolitan development, some amount of forests and vegetation have been replaced by impervious and artificial urban road surfaces, lead to increasing ambient temperature of many Malaysian urban areas. Urban greenery including roadside trees planting is believed to be a useful mitigation strategy of road surface temperature and thus the local ambient temperature. Malaysian cities appear to have different roadside roads conditions which help cooling the air and providing shade. Many researchers have suggested various environmentally methods to alleviate ambient air temperature by planting the vegetation in urban areas which are closely connected to the roads of a city. However, there is a lack of studies to concern influence factors of roadside trees and road characteristics on each other in the face of surface and air temperature reduction surrounding the road. This study first identifies a pattern on the effects of road characteristics, including road orientation and road width with an overview on the capabilities of roadside tree planting and road design to mitigate road surrounding microclimate. It then provides guidelines for urban development towards green roads in a tropical city.